CORRELATION BEHAVIOR OF MANTAINING ORAL AND DENTAL HEALTH AND ENVIRONMENTAL FACTORS WITH DENTAL CARIES IN 11-12 YEARS OLD CHILDREN IN SD NEGERI 1 AND MI NEGERI KALIKURMO BRINGIN SUBDISTRICT - Dandy Iqbal Saputra; Arwinda Nugraheni; Aras Utami; Avina Anin Nasia (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2021)
ABSTRACT Background: Oral and dental health problems in Indonesia still occur a lot. Poor oral and dental health will impact the individual by causing pain, reducing quality of life and decrease individual productivity. Caries is serious oral and dental health problem in society, therefore it needs attention and involvement from all parties to overcome it. Environmental factors are very important in maintaining oral and dental health and teaching healthy living behaviors.Objective: To determine the correlation behavior of maintaining oral and dental health and environmental factors with caries incidence in 11-12 years old children in Bringin Subdistrict. Methods: This study was an analytic observational study with cross sectional study approach. This research sample method using total sampling method. The sample used is all members of the population as many as 60 research subjects. This study consist of 4 assessment factors, there are the consumption level of cariogenic foods, tooth brushing habits, parents income level, and parents education. The results of this study are the scores of these four factors and the DMF-t index. Before participating In this research, subjects were asked to fill out a questionnaire and informed consent. Examination performed by using a sonde and mirror mouth. Results: There was a correlation on the results of chi square test on the level of education and cariogenic food consumption with caries status in 11-12 years old children in Bringin Subdistrict. P = 0.001 (P<0.05).Conclusion: There is a correlation on behavior of maintaining oral and dental health and environmental factors with dental caries in 11-12 years old children in SD 1 and MI N Kalikurmo, Bringin Subdistrict.